Analisis Kemampuan Berpikir Kritis Matematis Ditinjau dari Tipe Kepribadian dalam Menyelesaikan Soal Literasi dan Numerasi - Chaniago, Ziannisa Azvani; Awalludin, Subhan Ajiz (Fakultas Keguruan dan Ilmu Pendidikan Universitas Singaperbangsa, 2024)
Critical thinking is an essential outcome of the learning process and a crucial tool for knowledge growth. This study aims to analyze the mathematical critical thinking skills of students based on their personality types when solving problems involving literacy and numeracy. A qualitative research method with a descriptive approach was employed. Four informants from the 8th grade, representing extrovert and introvert personality types, participated in the study. Their personalities were identified using the Eysenck Personality Inventory (EPI) non-test instrument. Subsequently, a validated and reliable critical thinking assessment tool was administered. The findings indicate that overall, both extrovert and introvert students can fulfill the four indicators of critical thinking skills proposed by Facione (1990): interpretation, analysis, evaluation, and inference. Extrovert students excelled in the interpretation and analysis indicators, demonstrating their ability to comprehend and translate information from problems into mathematical models. However, extrovert students often made mistakes in the evaluation indicator, lacking accuracy in calculations and inferences. Conversely, introvert students met all four indicators of mathematical critical thinking skills and exhibited greater meticulousness, enabling them to answer questions in accordance with their intended purpose. Critical thinking, literacy, and numeracy are three interrelated and inseparable skills. Therefore, students with strong critical thinking skills are more likely to possess proficient literacy and numeracy skills as well.